Simulating the Impact of an Increase in Patient Volume on a Government Emergency Department in Malaysia - Norazura, Ahmad; Noraida, Abdul Ghani; Anton Abdulbasah, Kamil; Razman, Mat Tahar (2014)

(untitled)
This paper explores the potential of computer simulation model to assess the effect of patient increase to emergency department performance and the patient flow. A simulation model of emergency department is developed based on discrete event simulation and system dynamics modeling approach to capture the behavior of an integrated system. Several scenarios are conducted to help management determine the required resources due to patient volume increase that will not breach the national target time for patient to be attended to in emergency department. Results from the scenarios show that a 7% increase of patients affects most of the performance measures. In addition, medical assistants are the important resources in emergency department operations.